Occurrence of Garlic Rust in Mid Hill of Nepal - Timila, Ram D; Joshi, Sharada; Manandhar, Gyanu; Sharma, Sarala (Nepal Agriculture Research Journal, 2010)
DOI: 10.3126/narj.v6i0.3372 Nepal Agriculture Research Journal Vol.6 2005 pp.110-111